Biomarkers in Oncology - Pournima Morey, Seema M. Jadhav, Manisha Karpe, Vilasrao Kadam (Journal of Applied Pharmaceutical Science)
A biomarker or biological marker is in general a substance used as an indicator of biological state. Biomarkers are characteristic biological properties that can be detected and measured in parts of the body like the blood or tissue. They may indicate either normal or diseased processes in the body. Biomarkers can be specific cells, molecules, or genes, gene products, enzymes, or hormones. As an important biological indicator of cancer status and progression for the physiological state of the cell at a specific time, biomarkers represent powerful tools for monitoring the course of cancer and gauging efficacy and safety of novel therapeutic agents. The recent progress of proteomics has opened new avenues for cancerrelated biomarker discovery. Advances in proteomics are contributing to the understanding of pathophysiology of neoplasia, cancer diagnosis, and anticancer drug discovery. One of the major contributions proteomics has made to the medical and pharmaceutical communities is the identification of potential drug targets.
Keywords: Biomarkers,carcinoma,peptides,proteomics,genomics,analytical analysis.